2017
DOI: 10.1103/physreve.96.053109
|View full text |Cite
|
Sign up to set email alerts
|

Front propagation in a regular vortex lattice: Dependence on the vortex structure

Abstract: We investigate the dependence on the vortex structure of the propagation of fronts in stirred flows. For this, we consider a regular set of vortices whose structure is changed by varying both their boundary conditions and their aspect ratios. These configurations are investigated experimentally in autocatalytic solutions stirred by electroconvective flows and numerically from kinematic simulations based on the determination of the dominant Fourier mode of the vortex stream function in each of them. For free la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(32 citation statements)
references
References 49 publications
2
30
0
Order By: Relevance
“…In our simulations we have used no-slip boundary conditions where the fluid velocity at all walls is zero. It is interesting to point out that recent experiments studying propagating fronts in cellular electroconvective flows probed the role vortex structure by using rigid and free boundaries and found that the fronts were faster for free boundary conditions [21]. In addition, the nondimensional parameters of our simulations span a range of values that include regions where the approximations of the theoretical predictions become questionable.…”
Section: Fronts Propagating In Straight-parallel Convection Rollsmentioning
confidence: 97%
See 2 more Smart Citations
“…In our simulations we have used no-slip boundary conditions where the fluid velocity at all walls is zero. It is interesting to point out that recent experiments studying propagating fronts in cellular electroconvective flows probed the role vortex structure by using rigid and free boundaries and found that the fronts were faster for free boundary conditions [21]. In addition, the nondimensional parameters of our simulations span a range of values that include regions where the approximations of the theoretical predictions become questionable.…”
Section: Fronts Propagating In Straight-parallel Convection Rollsmentioning
confidence: 97%
“…This may be due, in part, to the variation of the vortex structure of the cellular flow for the different boundary conditions as explored in Ref. [21].…”
Section: Fronts Propagating In Straight-parallel Convection Rollsmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting situation to highlight the implication of advection on front propagation relates to steady closed flows (Audoly, Berestycki & Pomeau 2000;Abel et al 2001Abel et al , 2002Cencini et al 2003;Vladimirova et al 2003;Paoletti & Solomon 2005;Pocheau & Harambat 2006, 2008Mahoney et al 2012;Tzella & Vanneste 2014, 2015Beauvier, Bodea & Pocheau 2016, 2017. Then, as streamlines are confined to compact regions, no large-scale advection of the medium and thus no net kinematic effect are expected at long times on fluid particles.…”
Section: Introductionmentioning
confidence: 99%
“…In the inviscid case, 2D flow conserves not only energy but also enstrophy (squared vorticity), giving rise to simultaneous turbulent cascades of energy to large length scales and enstrophy to small length scales [2][3][4]. Furthermore, 2D or quasi-2D flows provide useful models for exploring new physical insights from ideas like Lagrangian coherent structures (LCSs) [5][6][7], exact coherent structures (ECSs) [8,9], transfer of energy and enstrophy among length scales [10][11][12][13], and advection-reaction-diffusion mechanisms [14][15][16][17][18][19], because 2D simulations demand far less computational power than 3D simulations and making high-resolution measurements throughout an experimental domain is far easier in 2D than in 3D. Analysis is also less computationally demanding in 2D than in 3D, whether the data of interest came from simulation or laboratory experiment.…”
Section: Introductionmentioning
confidence: 99%